2021
DOI: 10.1053/j.gastro.2020.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Exome-Wide Association Study on Alanine Aminotransferase Identifies Sequence Variants in the GPAM and APOE Associated With Fatty Liver Disease

Abstract: BACKGROUND & AIMS: Fatty liver disease (FLD) is a growing epidemic that is expected to be the leading cause of end-stage liver disease within the next decade. Both environmental and genetic factors contribute to the susceptibility of FLD. Several genetic variants contributing to FLD have been identified in exome-wide association studies. However, there is still a missing hereditability indicating that other genetic variants are yet to be discovered. METHODS: To find genes involved in FLD, we first examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 75 publications
8
114
2
2
Order By: Relevance
“…We hypothesised that germline variation providing weaker modulation of disease phenotypes would exist and might improve the performance of polygenic risk scores being developed for prognostication in NAFLD and ARLD. Amongst these genes, germline coding variants GPAM have been associated with serum ALT levels in an exome-wide association study of the UK Biobank cohort [16]. Further study found that these variants were also associated with hepatic fat content and histological markers of liver damage in independent NAFLD cohorts.…”
Section: Introductionmentioning
confidence: 94%
“…We hypothesised that germline variation providing weaker modulation of disease phenotypes would exist and might improve the performance of polygenic risk scores being developed for prognostication in NAFLD and ARLD. Amongst these genes, germline coding variants GPAM have been associated with serum ALT levels in an exome-wide association study of the UK Biobank cohort [16]. Further study found that these variants were also associated with hepatic fat content and histological markers of liver damage in independent NAFLD cohorts.…”
Section: Introductionmentioning
confidence: 94%
“…[30][31][32][33] We are therefore presently moving to a model where, across the continuum of the distribution of the inherited predisposition to NAFLD in the population, the development of polygenic risk scores (PRS) can stratify the risk of this condition and of liver-related complications. 30,31,[34][35][36] For example, "high" PRS can predict the evolution to cirrhosis and HCC independently of classical risk factors in individuals with dysmetabolism and/or NAFLD, potentially being able to aid in the clinical management and in the design of referral pathways. 35 On the other hand, it has become clear that the main common risk variant and PRS cannot discriminate accurately between "metabolic" and "genetic" NAFLD.…”
Section: Role Of Genetic Determinantsmentioning
confidence: 99%
“… 14 17 28 29 Due to the increased power of studies conducted in large population-based cohorts, the number of NAFLD risk variants is now increasing by the day. 30 31 32 33 We are therefore presently moving to a model where, across the continuum of the distribution of the inherited predisposition to NAFLD in the population, the development of polygenic risk scores (PRS) can stratify the risk of this condition and of liver-related complications. 30 31 34 35 36 For example, “high” PRS can predict the evolution to cirrhosis and HCC independently of classical risk factors in individuals with dysmetabolism and/or NAFLD, potentially being able to aid in the clinical management and in the design of referral pathways.…”
Section: Role Of Genetic Determinantsmentioning
confidence: 99%
“…14,17,28,29 Due to the increased power of studies conducted in large population-based cohorts, the number of NAFLD risk variants is now increasing by the day. [30][31][32][33] We are therefore presently moving to a model where, across the continuum of the distribution of the inherited predisposition to NAFLD in the population, the development of polygenic risk scores (PRS) can stratify the risk of this condition and of liver-related complications. 30,31,[34][35][36] For example, "high" PRS can predict the evolution to cirrhosis and HCC independently of classical risk factors in individuals with dysmetabolism and/or NAFLD, potentially being able to aid in the clinical management and in the design of referral pathways.…”
Section: Role Of Genetic Determinantsmentioning
confidence: 99%
“…[30][31][32][33] We are therefore presently moving to a model where, across the continuum of the distribution of the inherited predisposition to NAFLD in the population, the development of polygenic risk scores (PRS) can stratify the risk of this condition and of liver-related complications. 30,31,[34][35][36] For example, "high" PRS can predict the evolution to cirrhosis and HCC independently of classical risk factors in individuals with dysmetabolism and/or NAFLD, potentially being able to aid in the clinical management and in the design of referral pathways. 35 On the other hand, it has become clear that the main common risk variant and PRS cannot discriminate accurately between "metabolic" and "genetic" NAFLD.…”
Section: Role Of Genetic Determinantsmentioning
confidence: 99%